INVASI AKASIA BERDURI (ACACIA NILOTICA) (L.) WILLD EX DEL. DI TAMAN NASIONAL BALURAN JAWA TIMUR DAN STRATEGI PENANGANANNYA - Djufri - (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2009)
Acacia nilotica is a thorny wattle native species in India, Pakistan and much of Africa. This Acacia is widely distributed in tropical and subtropical Africa from Egypt and Mauritania to South Africa. The invasion of A. nilotica has resulted in the reduction of savannah wide in Baluran National Park reaching about 50%. Presure to the savannah has a great impact on the balance and preservation of whole ecosystem in Baluran. Some efforts have been to fight against the wide-spreading of invasion of A. nilotica for example eradication chemically use Indamin 72 HC and 2,4 D Dinitropenol, but result is not effective. And so it is with eradication in the mechanic use bulldozer appliance, and cut away to burn, not yet given optimal result, proven invasion of A. nilotica in this time not yet deductible, exactly growing wide. For the reason, require to be looked for alternative is way of the other eradication, so that the wide-spreading of preventable invasion A. nilotica. Otherwise hence the possibility of big savannah exist in National Park of Baluran metamorphose to become forest of A. nilotica.Â Kata kunci: invasi, akasia berduri, dan strategi penanganan.Â